Akkermansia muciniphila Enhances the Antitumor Effect of Cisplatin in Lewis Lung Cancer Mice - Zhuo Chen; Xiang Qian; Shasha Chen; Xiaoxuan Fu; Guanjun Ma; Aiqin Zhang (Journal of Immunology Research)
Recently, intestinal flora plays a vital role in the occurrence and development of tumors and there is link between cancer immunotherapy and Akkermansia muciniphila (Akk). However, the therapeutic efficacy of Akk in lung cancer remained unclear. Hence, our study is aimed at investigating the antitumor effects of cisplatin (CDDP) combined with Akk on lung cancer. Using the murine lung cancer model by subcutaneously inoculating Lewis lung cancer model, 50 mice were divided into five groups: normal, model, CDDP, CDDP+Akk, and CDDP+antibiotics. After treatment within 5 weeks, compared with the model group, the administered group improved the changes of tumor pathomorphology. Compared with the CDDP group, CDDP combining with Akk slowed down the growth of tumor volume, downregulated the levels of ki-67, p53, and factor-associated suicide (Fas) ligand proteins and upregulated Fas proteins, increased the levels of interferon-γ, interleukin-6, and tumor necrosis factor-α, and suppressed the expression of CD4+CD25+Foxp3+ Treg in mouse peripheral blood and spleen. In addition, transcriptome analysis indicated that Akk combining with CDDP increased obviously the levels of IFI27l2 and IGFBP7 and was related to those pathways including the cytokine-cytokine receptor interaction, Th17 cell differentiation, FOXO, JAK-STAT, and PI3K-Akt signaling pathways. These results suggested that the therapeutic efficacy of the combined treatment of Akk and CDDP was superior to the only CDDP treatment, which could enhance immune regulation and would be a promising strategy for the treatment of lung cancer.